120k views
4 votes
Given f(x) = 3x - 1 and 9(x) = 2x-3, for which value of x does g(x)=f(2)?

1 Answer

1 vote

Answer:

g(x) = f(2) at x = 4

Explanation:

Assuming that you meant g(x) = 2x - 3:

Set f(2) = g(x) and solve the resulting equation for x:

f(2) = 3(2) - 1 = g(x) = 2x - 3.

Thus, 6 - 1 = 2x - 3.

Adding 3 to both sides and simplifying the result, we get:

8 = 2x, or x = 4.

g(x) = f(2) at x = 4.

User Safeer
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.